The position of siyar on free trade: a historico-legal analysis - Ahamat, Haniff (Kluwer Law International, 2010)
This article examines how siyar can improve economic relations within and among Muslim States by liberalising and increasing trade. The notion of siyar historically presupposed strong trade relations within the Muslim community where Muslims and specific categories of non-Muslims from all parts of the Muslim world and beyond could trade anywhere with little or no restrictions. However, over quite a long period the development of siyar was stalled. In this light, a rather historical approach is chosen by the author. The article will first discuss what siyar is and what its role was in regulating the economic relations of the early Islamic State. The approach taken by siyar towards “free trade” as evidenced by the practices of the early Islamic State is introduced. A caveat has to be constructed that the concept of free trade as practised at that time must not be understood in exactly the same way as the term free trade that underscores the present day GATT/WTO system. While barriers to trade were erected not only by the early Islamic State but also by other States at that time, this research will aim to reach a conclusion as to whether a freer trade was and is desired by siyar. The article will look at the practices of later Islamic States, i.e. the Muslim dynasties which were established towards the end of the Abbasid period and thereafter, followed by a brief analysis of regulation of internal and external trade by the Ottoman Empire. Such discussions will include consideration whether the practices of those dynasties were consistent with what had been recommended by siyar. Finally the article looks at the challenges to reviving siyar trade rules following the collapse of the Ottoman Empire and the emergence of many separate Muslim-nation States in the twentieth century.